Impact of Mass Media on Attitude and Practice of Public Health Knowledge among Urban Population of Bangladesh - Nowshin, Iffat; Salim, Farhana; Rozario, Rini Juliet; Nazneen, Humaira (Eastern Medical College Journal, 2022)
This descriptive type of cross-sectional study was conducted among 180 persons of different socio-economic conditions of Dhaka city using semi-structured questionnaire through face-to-face interview to identify the impact of mass media in disseminating public health related messages to the urban population of Bangladesh. Convenience sampling was the process of selecting the subjects. Among 180 respondents mean age of the respondents was 28.75±8.55 years. Majority of the respondents were graduate (29.0%). Of the total 180 respondents 121 (67.2%) read newspaper and among them, 46 (38.32%) read Public Health related articles in the newspaper regularly. On the other hand out of the total 180 respondents 170 (95.0%) watch television and of them 36 (21.18%) watch public health related programme in the television regularly. Highest 140 (77.8%) respondents said television as the source of information in TB prevention. Majority (90%) of the respondents said of television as the information source on prevention of diarrhoeal diseases. Magazine and internet were mentioned by 20 (11%) respondents in each group as the information source. Regarding the sources of information on pregnancy related problems and solutions television was mentioned as the source of information by 156 (86%) of the respondents. Friends or relatives or teachers (67%), newspaper (64%), billboard (45%) and radio (44%) were other sources. Television was found as the main source of public health information to the people. Impact of print media in disseminating public health messages was mentioned very satisfactory by 24% and electronic media by 77% respondents. The mass media can be very much effective in getting public health messages to the community in developing countries. In view of our findings, it may be recommended that television, newspaper and billboards may be used as tools for reaching out that the use of these media should be strengthened further. EMCJ. January 2022; 7(1): 21-25